Risk of hematologic malignancies following herpes zoster after COVID-19: a global cohort study - Lu, Chien-Lin; Wang, Joshua; Ho, Ching-Liang; Wu, Yan-Jun; Lu, Kuo-Cheng; Yang, Chung-Chi (Frontiers in Medicine, 2025)
IntroductionHerpes zoster (HZ) has been reported as a potential post-viral complication in individuals recovering from COVID-19, possibly due to virus-induced immune dysregulation. We aimed to investigate whether post-COVID HZ is associated with an elevated risk of hematologic or infectious complications.MethodsWe conducted a retrospective cohort study using the TriNetX global research network, which aggregates de-identified electronic health records from more than 140 healthcare institutions. Adults diagnosed with COVID-19 between January 2020 and January 2022 were stratified by the presence or absence of HZ within one year of infection and matched 1:1 by age, sex, and comorbidities. Outcomes including leukopenia, urinary tract infection, multiple myeloma, and acute leukemia were evaluated over a three-year follow-up using time-to-event and multivariable Cox regression analyses.ResultsIndividuals with post-COVID HZ had significantly higher risks of developing hematologic and infectious complications. Subgroup analyses identified older age, impaired kidney function, elevated inflammatory markers, and metabolic abnormalities as factors associated with greater risk.DiscussionThese findings suggest that HZ following COVID-19 may serve as a clinical indicator of immune vulnerability and heightened susceptibility to hematologic and infectious disorders. Long-term monitoring may be warranted in high-risk populations.